Pengaruh Stres terhadap Kesejahteraan Psikologis Mahasiswa selama Pembelajaran Jarak Jauh di Masa Pandemi Covid-19 - Novia Nanda, Gusti; Pradna Paramita, Pramesti (Jurnal Syntax Fusion, 2022)
Based on Circular Number 1 of 2020 concerning the Prevention of the Spread of Corona Virus Disease (COVID-19) in universities, during the COVID-19 pandemic, leaders of State Universities (PTN) and Higher Education Service Institutions (LLDikti) were asked to adjust the implementation of the Tri Dharma College by conducting distance learning. Compared to the general population, university students are more vulnerable to mental health problems stemming from a pandemic due to the various changes taking place in the learning system. This study aims to determine whether student stress affects psychological well-being during distance learning during the COVID-19 pandemic. This research was conducted on students at public and private universities with a total of 273 respondents. The value of the coefficient of determination (R²) is 0.089, which means that the stress variable has an effect of 8.9% on the psychological well-being of students, while 91.1% comes from other variables not examined. It is also known that the regression coefficient value is -1.48, which states that for every 1% addition to the stress value, the psychological well-being value decreases by -1.481. Therefore, it is expected that students can take preventive steps so as not to experience stress during distance learning, because stress can be one of the causes of disruption of psychological well-being.